Diclofenac sodium and prednisolone acetate ophthalmic solution in controlling inflammation after cataract surgery - Hossain, MM; Mohiuddin, AA; Hossain, MA; Aziz, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):343-7. The abstract of this article is available on the PubMed website